Experimental Evaluation of Fluid Dynamic and Thermal Behaviors in Compact Heat Exchanger with Aluminum Foam. (November 2016) - Cicala, Giusi; Cirillo, Luca; Diana, Alessandra; Manca, Oronzio; Nardini, Sergio
Abstract: In this paper an experimental investigation on forced convection in a compact heat exchanger made up with an aluminum foam plate of 212.5 mm x 212.5 mm with a thickness of 40 mm and a single array with five circular tubes is presented. The foam has a porosity of 0.93 with 10, 20 and 30 pores per inch and the tubes in aluminum have internal and external diameters equal to 9.5 mm and 12.5 mm. The test rig consists of an open air channel and a closed water cycle and the aluminum foam plate is placed inside the channel. The performances of the compact heat exchanger are evaluated for assigned hot water mass flow rate and different hot water inlet temperatures and air mass flow rate. Results are given in terms of heat transfer rates and pressure drops as a function of air velocity and Reynolds numbers. The evaluation of dimensionless, Colburn factor and Nusselt number is performed for different air mass flow rates and hot water inlet temperatures.